The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.est.0c02834
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Omics Elucidate the Mechanisms Driving the Rapid Biodegradation of Deepwater Horizon Oil in Intertidal Sediments Undergoing Oxic–Anoxic Cycles

Abstract: Crude oil buried in intertidal sands may be exposed to alternating oxic and anoxic conditions but the effect of this tidally induced biogeochemical oscillation remains poorly understood, limiting the effectiveness of remediation and managing efforts after oil spills. Here, we used a combination of metatranscriptomics and genome-resolved metagenomics to study microbial activities in oil-contaminated sediments during oxic–anoxic cycles in laboratory chambers that closely emulated in situ conditions. Approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…S2). Consistent with these expectations, we observed a high degree of similarity between the microbial communities in the chambers when inoculated with DWH oil and the previous field samples [12], further validating our mesocosm as tools to reliably study in situ microbial processes. For the present study, generalist taxa were defined as operational taxonomic units (OTU) having broad niche breadth reflected by increased number of non-redundant protein functions (measured as the number of molecular function gene-ontology -GOterms), whereas specialist taxa were defined as OTUs having a narrow niche breadth characterized by fewer nonredundant protein functions.…”
Section: Pensacola Fieldsupporting
confidence: 84%
“…S2). Consistent with these expectations, we observed a high degree of similarity between the microbial communities in the chambers when inoculated with DWH oil and the previous field samples [12], further validating our mesocosm as tools to reliably study in situ microbial processes. For the present study, generalist taxa were defined as operational taxonomic units (OTU) having broad niche breadth reflected by increased number of non-redundant protein functions (measured as the number of molecular function gene-ontology -GOterms), whereas specialist taxa were defined as OTUs having a narrow niche breadth characterized by fewer nonredundant protein functions.…”
Section: Pensacola Fieldsupporting
confidence: 84%
“…Available metatranscriptomic data from the field (Mason et al ., 2012) or laboratory mesocosm incubation experiments mimicking in situ pressure gradients in beach sands consistently showed that the genes associated with the DWH‐clade alkB operon were expressed significantly higher in oiled vs. clean/control samples (log2fold change 2.728, p‐adj = 0.01). Briefly, the laboratory mesocosm involved advective flow chambers incubated with weathered DWH oil and were followed over time with metagenomic and metatrancriptomics sequencing and were described previously by our team (Karthikeyan et al ., 2020c). Importantly, a comparison to field samples showed that these mesocosm samples represented well the coastal sediments and that most added DWH oil was degraded within a period of 3 months although some aromatic and complex hydrocarbon constituents remained at the end of the incubation (Karthikeyan et al ., 2020c).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the laboratory mesocosm involved advective flow chambers incubated with weathered DWH oil and were followed over time with metagenomic and metatrancriptomics sequencing and were described previously by our team (Karthikeyan et al ., 2020c). Importantly, a comparison to field samples showed that these mesocosm samples represented well the coastal sediments and that most added DWH oil was degraded within a period of 3 months although some aromatic and complex hydrocarbon constituents remained at the end of the incubation (Karthikeyan et al ., 2020c). Notably, DWH‐clade genes were present at ~10× and ~8× higher abundances compared with the control (no oil added) and the non DWH‐clade associated genes in the laboratory mesocosms samples, respectively, especially during the later stages of oil degradation when longer aliphatic and aromatic hydrocarbons were enriched (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrocarbon utilizers reproduce rapidly in the presence of oil to dominate the microbial ecosystem in contaminated waters and sediments, creating a microbial bloom (Kostka et al, 2011;Doyle et al, 2018Doyle et al, , 2020Karthikeyan et al, 2019). Many oil-degrading microbes possess multiple pathways for hydrocarbon degradation, and which metabolic pathway is induced may depend on environmental conditions and type of exposure (Karthikeyan et al, 2020a).…”
Section: Oil-degrading Microbial Collaboration and Community Dynamicsmentioning
confidence: 99%
“…In short order, the DWH spill caused major shifts in microbial ecosystem structure and function. Rare biosphere species capable of degrading hydrocarbons rapidly outgrew neighbors, ultimately accounting for up to 90% of the community (Kleindienst et al, 2015a;Karthikeyan et al, 2019Karthikeyan et al, , 2020a. At the same time, microbes that typically dominate healthy environmental systems, such as ammonia oxidizers and other autotrophs and heterotrophs, declined in relative abundance.…”
Section: Oil-degrading Microbial Collaboration and Community Dynamicsmentioning
confidence: 99%